Estimation of loss in yield due to Sigatoka leaf spot disease of banana cv. Rajapuri (Musa AAB) - SRI KANT KULKARNI and P.B. PATIL, N. THAMMAIAH, M.S. KULKARNI (Indian Phytopathology, 2005)
The estimation of loss in yield due to Sigatoka leaf spot disease was carried out during 2001- 2003. The results showed that, the control receiving no chemical spray recorded the maximum POI in both main crop (41.38%) and first ratoon crop (64.48%). The lowest yield was recorded in control (15.82 t/ha and 19.41 t/ha in main crop and the first ratoon crop, respectively). The loss in yield due to Sigatoka leaf spot was maximum (24.44%) in the control, whereas it was 14.54 percent and 6.94 percent in the treatment of one spray of carbendazim 0.1 percent and two sprays of carbendazim 0.1 per cent, respectively.